2022
DOI: 10.1590/fst.66121
|View full text |Cite
|
Sign up to set email alerts
|

A pivotal peptide (Ile-Leu-Lys-Pro) with high ACE- inhibitory activity from duck egg white: identification and molecular docking

Abstract: Salted duck egg white was desalted and hydrolyzed to produce angiotensin I-converting enzyme (ACE) inhibitory peptides. Single factor test and response surface design were performed to determine the best hydrolysis conditions: enzyme dosage 11875.99 U/g, substrate concentration 33.04 g/L and hydrolysis time 4 h. The fraction V (M W < 1 kDa), which exhibited the strongest ACE inhibitory activity, was characterized by HPLC-ESI-MS/MS. Eighty-three peptides were identified, and among them Ile-Leu-Lys-Pro, Ile-Asn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…(2023) reported significant inhibition of ACE activity by leucine. Furthermore, highly active ACEIPs isolated from egg white protein (Adli et al., 2023; Li et al., 2022; Yu et al., 2023), squid muscle protein (Fan & Wu, 2021), and silkworm pupa protein (Liang et al., 2018) contain leucine. The characteristics of the active peptides identified in this study align with the structural features of peptides with high ACE inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…(2023) reported significant inhibition of ACE activity by leucine. Furthermore, highly active ACEIPs isolated from egg white protein (Adli et al., 2023; Li et al., 2022; Yu et al., 2023), squid muscle protein (Fan & Wu, 2021), and silkworm pupa protein (Liang et al., 2018) contain leucine. The characteristics of the active peptides identified in this study align with the structural features of peptides with high ACE inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…The types and amounts of these amino acids play an important role in the overall antioxidant ability of peptides. Some studies seemingly suggest that peptides containing Tyr and Trp at the C-terminal can show strong free radical-scavenging ability, while amino acids such as Ser and Ile can show high free radical-scavenging ability at both the N-terminal and the C-terminal of the peptide (Li et al, 2022;Nisov et al, 2020). The increase of these special functional amino acids among the proteolysis products of burley tobacco is an important reason for the improvement of its antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive peptides hydrolyzed from protein are the general term for 2-peptides to complex peptides composed of amino acids. Modern nutritional studies have pointed out that bioactive peptides hydrolyzed from protein can be more effectively absorbed by the body, thereby playing a specific role or improving the growth of intestinal flora to provide probiotic effects (Ji et al, 2022;Li et al, 2022;Tekle et al, 2022;Wei et al, 2022). For example, Ruann J. S. de Castro and Hélia H. Sato found that soy protein isolate hydrolysate had a 7-fold enhanced antioxidant activity compared with soy protein isolate (Castro & Sato, 2014).…”
Section: Frontier Research Direction Of Ebnmentioning
confidence: 99%